2021
DOI: 10.1158/0008-5472.can-20-2769
|View full text |Cite
|
Sign up to set email alerts
|

miR-31 Displays Subtype Specificity in Lung Cancer

Abstract: miRNA rarely possess pan-oncogenic or tumor-suppressive properties. Most miRNAs function under tissue-specific contexts, acting as either tumor suppressors in one tissue, promoting oncogenesis in another, or having no apparent role in the regulation of processes associated with the hallmarks of cancer. What has been less clear is the role of miRNAs within cell types of the same tissue and the ability within each cell type to contribute to oncogenesis. In this study, we characterize the role of one such tissue-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The literature on miR-31 is quite controversial, as this particular miRNA appears to be downregulated in certain types of cancer, such as liver [ 137 ], prostate [ 138 ], and triple negative breast cancer [ 139 ], but upregulated in colorectal [ 140 ], cervical [ 141 ], rectal [ 142 ], and certain subtypes of lung cancer [ 143 ], suggesting that the mode of miR-31 regulation depends on cancer histology. Overall, in HNC, miR-31 mostly appears to be upregulated [ 46 , 47 , 79 , 144 , 145 , 146 ], acting as an oncogene and promoting the proliferation and invasion of tumor cells [ 147 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…The literature on miR-31 is quite controversial, as this particular miRNA appears to be downregulated in certain types of cancer, such as liver [ 137 ], prostate [ 138 ], and triple negative breast cancer [ 139 ], but upregulated in colorectal [ 140 ], cervical [ 141 ], rectal [ 142 ], and certain subtypes of lung cancer [ 143 ], suggesting that the mode of miR-31 regulation depends on cancer histology. Overall, in HNC, miR-31 mostly appears to be upregulated [ 46 , 47 , 79 , 144 , 145 , 146 ], acting as an oncogene and promoting the proliferation and invasion of tumor cells [ 147 ].…”
Section: The Role Of the Most Common Mirnas In Hncmentioning
confidence: 99%
“…The highest-weight microRNAs in the model correspond to hsa-miR-31, which is associated in our data with shorter survival. This miR is known to promote tumor growth and correlates with low survival in previous studies (Davenport et al 2021; Edmonds et al 2016; Tan et al 2011). By contrast, hsa-miR-34 is associated in our model with longer survival.…”
Section: Discussionmentioning
confidence: 75%
“…This phenomenon can be explained because a single miRNA triggers a variety of targets that in turn activate different signaling pathways. Indeed, a recent study demonstrated that miR-31 had different functional roles across lung cancer subtypes by activating different signaling pathways [ 32 ].…”
Section: Discussionmentioning
confidence: 99%